2012
DOI: 10.1371/journal.pone.0031367
|View full text |Cite|
|
Sign up to set email alerts
|

The Transcriptional Response of Caenorhabditis elegans to Ivermectin Exposure Identifies Novel Genes Involved in the Response to Reduced Food Intake

Abstract: We have examined the transcriptional response of Caenorhabditis elegans following exposure to the anthelmintic drug ivermectin (IVM) using whole genome microarrays and real-time QPCR. Our original aim was to identify candidate molecules involved in IVM metabolism and/or excretion. For this reason the IVM tolerant strain, DA1316, was used to minimise transcriptomic changes related to the phenotype of drug exposure. However, unlike equivalent work with benzimidazole drugs, very few of the induced genes were memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
45
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 51 publications
(64 reference statements)
4
45
1
1
Order By: Relevance
“…They include genes associated with fatty acid metabolism (fat-3, fat-7, far-7, and acs-17) and cyp-37B1 and scl-2 (thought to be associated with fat storage). In our study, fat-2 and fat-3 were upregulated and fat-7 downregulated as was the case after exposure to ivermectin (27). However, we have found that a fat-3 deletion mutant is refractory to biofilm formation.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…They include genes associated with fatty acid metabolism (fat-3, fat-7, far-7, and acs-17) and cyp-37B1 and scl-2 (thought to be associated with fat storage). In our study, fat-2 and fat-3 were upregulated and fat-7 downregulated as was the case after exposure to ivermectin (27). However, we have found that a fat-3 deletion mutant is refractory to biofilm formation.…”
Section: Discussionsupporting
confidence: 55%
“…Since Y. pseudotuberculosis forms biofilm around the head of C. elegans blocking the mouth, it is possible that the worm may respond by inducing genes associated with reduced food uptake. Previously, Laing et al (27) showed that exposure of C. elegans to the nematocidal drug ivermectin results in the induction of many genes associated with starvation. A comparison of the numbers of genes associated with biofilm formation and ivermectin treatment is summarized in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of wide-scale studies have been carried out to investigate transcriptional responses of C. elegans to a variety of different chemical exposures, including anthelmintics [39][41], insecticides [42], polychlorinated biphenyls [43], vertebrate steroids [44] and juglone [45]. Whilst these studies have identified a number of upregulated transcripts (particularly from the families involved in cellular metabolism) they have usually involved exposures to relatively few compounds.…”
Section: Introductionmentioning
confidence: 99%
“…IVM is a macrocyclic lactone, which irreversibly binds to and activates ligand-gated chloride channels, resulting in paralysis of the body wall and pharyngeal muscles [13]. IVM has been shown to induce the expression of a notably different subset of genes in C. elegans, particularly those associated with fat metabolism, thought to reflect a fasting response [14]. The effect of these anthelmintics on the stability of commonly used RGs in H. contortus has not been described.…”
Section: Introductionmentioning
confidence: 99%